The enigma of early progesterone rise: Is it associated with the type of gonadotropin used? - Abhijit A Oka; Gauri A Oka (Journal of Human Reproductive Sciences, 2019)
Background: It is debated whether the use of recombinant follicle-stimulating hormone (r-FSH) or human menopausal gonadotropin (HMG) is associated with progesterone (P) elevation in the late follicular phase. Aims: The aim is to determine whether the type of gonadotropin used for controlled ovarian stimulation (COS) in in vitro fertilization (IVF) is associated with P elevation in the late follicular phase using antagonist protocol. Setting and Design: This was a retrospective data analysis in the IVF unit. Methods: Data of women who underwent COS between January 2005 and December 2017. Statistical Analysis: Chi-square and unpaired Student's t-test in SPSS 20. Results: Data of 439 women was analyzed. Mean age was 31.45 ± 4.6 years. HMG was used in 193 (44%), r-FSH in 232 (52.8%), and a combination of both in 14 (3.2%) women. Proportion of women with elevated P was significantly higher in r-FSH group as compared to HMG group (19/232 [8.2%] vs. 6/193 [3.1%]; P= 0.027). Mean P levels were significantly higher in r-FSH group (0.75 ng/ml vs. 0.59 ng/ml; P = 0.049). Mean estradiol (E2) levels at trigger were significantly higher in women with elevated P as compared to normal P(2893.4 ± 2091.8 pg/ml vs. 1668.3 ± 1508.6 pg/ml respectively; P< 0.000). Fresh embryo transfers performed in 18/27 women with elevated P resulted in pregnancy in three (16.7%) women. Two had biochemical pregnancies and one was lost to follow-up. Conclusions: Use of r-FSH and E2 levels at trigger are associated with elevated P levels in the late follicular phase. Fresh embryo transfers performed in spite of elevated P levels were associated with low pregnancy rates and unfavorable outcomes.